ANALISIS RASIO UNTUK MENGUKUR KINERJA KEUANGAN PEMERINTAH KOTA PALU - Singi, Nirmala (Katalogis, 2018)
The purpose of this reseach are: (1) To determine and analyze the financial performance of Palu City Government based on independence ratio in fiscal year of 2008-2015. (2) To determine and analyze financial performance of  Palu City based on effectiveness ratio of budget year 2008-2015. 3) To determine and analyze the financial performance of Palu City Government based on growth ratio of budget year 2008 - 2015.Type of study is descriptive by using secondary data in the form of realization report of revenue and expenditure budget of City Palu government in year 2008 - 2015. Wich is taken  from BPKAD office Palu City. Method of data analysis  used are independence ratio, effectiveness ratio and growth ratio.The result underline that the independence ratio of Palu City Government reflects instructive relationship with low financial ability that range 0-25%. The effectiveness ratio achieved by the Government of Palu quite good. The growth ratio is  fluctuated general.